IMPACT OF THE IMPLEMENTATION OF THE QUALITY MANAGEMENT SYSTEM ON THE QUALITY OF EDUCATION OF MEDICAL HIGHER EDUCATION INSTITUTIONS (Marketing Journal, 2025)
214 This article analyzes the content of large -scale reforms aimed at improving the quality of education in higher education institutions. The study highlights the impact of improving the quality management system on the overall quality of education and the co mpetitiveness of institutions. It is emphasized that, in the process of developing quality management systems in modern higher education institutions, it is essential to view students as direct consumers of educational services. From this perspective, oppo rtunities for improving the quality of educational services through the enhancement of curricula and study plans, making necessary adjustments, anticipating emerging needs and demands, and integrating them into the educational process are examined. The art icle also scientifically demonstrates the adaptability of the quality management system to changes in the educational services market and its role in ensuring the competitiveness of higher education institutions.
Keywords: education; quality; educational services market; competitiveness; quality management; consumer; medical education